2018
DOI: 10.1002/aps3.1157
|View full text |Cite
|
Sign up to set email alerts
|

Internal transcribed spacer 2 (ITS2) barcodes: A useful tool for identifying Chinese Zanthoxylum

Abstract: Premise of the StudyThe genus Zanthoxylum in the Rutaceae family of trees and shrubs has a long history of domestication and cultivation in Asia for both economic and medicinal purposes. However, many Zanthoxylum species are morphologically similar and are easily confused. This often leads to false authentication of source materials and confusion in herbal markets, hindering their safe utilization and genetic resource conservation. DNA barcoding is a promising tool for identifying plant taxa.MethodsWe used thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Citrus [24]. However, at the cultivar level, this technique often fails to yield clear results, as exemplified by the study on Zanthoxylum by Zhao et al [25]. Nevertheless, the findings of the present study indicate that at the level of both species and variety, there appears to be relatively low genetic diversity among the three species Z. bungeanum, Z. armatum, and Z. piperitum.…”
Section: Genetic Diversity Assessmentmentioning
confidence: 51%
See 1 more Smart Citation
“…Citrus [24]. However, at the cultivar level, this technique often fails to yield clear results, as exemplified by the study on Zanthoxylum by Zhao et al [25]. Nevertheless, the findings of the present study indicate that at the level of both species and variety, there appears to be relatively low genetic diversity among the three species Z. bungeanum, Z. armatum, and Z. piperitum.…”
Section: Genetic Diversity Assessmentmentioning
confidence: 51%
“…2a. 25,520 isogenes were annotated to one of these five pathways. Of those isogenes annotated, the highest number (12,085) were assigned to cohort A and accounted for 47.36% all isogenes.…”
Section: Kegg Pathwaysmentioning
confidence: 99%
“…Zanthoxylum formed a phylogenetic group in previous molecular phylogenetic studies [5,15,16]; however, these studies did not sufficiently resolve the relationships among some of its taxa. These studies were based on the ITS sequences of nuclear ribosomal DNA and the trnL-trnF, matK-trnK, atpB, atp-rbcL, and rbcL sequences of the cp genome [23][24][25]. Although these regions were considered to be universal DNA barcodes for higher plants, they did not allow the assessment of the usefulness of these loci in the barcoding of some taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature showed that the ITS-2 region has been used as a genetic marker for scrutinizing the diversity and exploring phylogenetic relationships 17 among astigmatid mites. ITS-2 marker has been used to successfully verify the taxonomy of closely related species and to differentiate and identify 18,19 different species of astigmatid mites. In this study, we used ITS-2 region to characterize astigmatid mites i.e.…”
Section: Phylogenetic Analysis Of Astigmatid Mites Sarcoptes Scabiei mentioning
confidence: 99%